Realizing simultaneous toughening and reinforcement in polypropylene blends via solid die-drawing. (14th January 2019) - Wu, Pingping; Yang, Qi; Zhao, Zhongguo; Zhang, Tongying; Huang, Yajiang; Liao, Xia
Abstract: High orientation structure in die-drawing products ensures excellent tensile strength and stiffness along the drawing direction but extremely poor toughness and ductility. Poly (ethylene-co-octene) (POE) was used to toughen orientated polypropylene (PP) prepared by die-drawing. However, the enhancement of toughness is at the expense of stiffness of matrix. To efficiently reserve the stiffness of PP matrix, high density polyethylene (HDPE) as auxiliary modifier, together with network structure through crosslinking and highly orientated structure through die-drawing process were applied. Specially, two different crosslinking strategies namely one-step and two-step crosslinking were compared. The results revealed that the combination of HDPE, POE and crosslinking reaction could realize simultaneous toughening and reinforcement of die-drawing PP blends. The tensile strength, modulus and impact strength of two-step crosslinking PP/POE/HDPE were 88.0 MPa, 1.7 GPa and 42.9 kJ/m 2 respectively after die-drawing, nearly three times in strength and even ten times higher in impact strength than raw PP. Graphical abstract: Highlights: This is the first report of realizing simultaneous toughening and reinforcement of polypropylene through solid die-drawing. The impact strength of polypropylene increases nearly 1000% than raw PP resin at relatively low elastomer content. The first study combines crosslinking and solid die drawing in polymer processing. Two-step crosslinking is much better than one-step crosslinking strategy for the final comprehensive performance of blends.